Production of Bambusa vulgaris seedlings from rhizomes under brackish water irrigation - Lourenço M. C. Branco; Claudivan F. de Lacerda; Albanise B. Marinho; Carlos H. C. de Sousa; Amanda S. F. Calvet; Erasto G. de Oliveira (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The objective of this study was to evaluate the influence of irrigation with brackish water on the production of bamboo seedlings (Bambusa vulgaris). The experiment was carried out at the Fazenda Experimental Piroás, in the municipality of Redenção, CE, Brazil (4° 14’ 53” S, 38° 45’ 10” W, and altitude of 230 m), in a completely randomized design with five treatments and six repetitions. The treatments consisted of five irrigation water electrical conductivity (ECw): 0.5 (control); 1.5; 2.5; 3.5 and 4.5 dS m-1. At 120 days after the beginning of the application of the treatments the leaf gas exchange, relative chlorophyll index (RCI), plant height (H), shoot dry matter (SDM), H/SDM ratio, and the concentrations of Na+ and K+ in stems and leaves were evaluated. Salt tolerance indexes were calculated based on SDM, H, photosynthesis rate and RCI. The increase in the ECw reduced leaf gas exchange, and the reduction in the photosynthesis rate was caused by stomatal and non-stomatal effects. The salinity affected negatively the growth and quality of bamboo seedlings, with the greatest effects being with ECw equal to or greater than 2.5 dS m-1. Bamboo seedlings present Na+ retention in the stems and low Na+/K+ ratio in the leaves. Bamboo seedlings are tolerant to salinity up to 1.5 dS m-1, indicating that waters with this salinity can be used for seedling production of this species, without loss of growth and quality.